Would the utilization of sFlt-1/PlGF ratio in clinical practice prevent unnecessary hospital admissions of cases with preeclampsia? - Majed Alhudhud; Hina Yousuf; Hanan Aljohani; Salwa Ibrahem; Shazia Maqsood; Rifat Shahin (Hypertension in Pregnancy)
Objectives Preeclampsia (PET) is a serious pregnancy complication with potential adverse maternal and fetal outcomes. Recent research has examined the soluble fms-like tyrosine kinase 1 (sFlt-1)/placental growth factor (PlGF) ratio for predicting PET. The study aimed to assess the efficacy of the sFlt-1/PlGF ratio in ruling out unnecessary hospital admission and PET.Methods sFlt-1/PlGF ratio was performed in patients as clinically indicated.Results The sFlt-1/PlGF ratio at a cutoff value of 51 predicted hospital admission with AUC, PPV, NPV, sensitivity, and specificity of 85%, 44%, 98%, 88%, and 85%, respectively. Additionally, at a cutoff value of 38, the sFlt-1/PlGF ratio predicted the short-term development of PET with PPV, NPV, sensitivity, and specificity of 42%, 100%, 100%, and 81%, respectively. The PlGF alone at a cutoff value of 193.36 predicted hospital admission with AUC, PPV, NPV, sensitivity, and specificity of 87%, 80%, 97%, 67%, and 98%, respectively. Moreover, at a cutoff value of 51.35, the PlGF alone predicted the development of PET with PPV, NPV, sensitivity, and specificity of 54%, 98%, 88%, and 90%, respectively. There was a significant association between a high sFlt-1/PlGF ratio and developing PET.Conclusion The sFlt-1/PlGF ratio and PlGF are promising for ruling out PET and hospital admission in pregnant women.